PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN, DAN PERPUTARAN AKTIVA TETAP TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI DASAR & KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - Widia Praptiwi, SE., Ak., M.Ak. , CA. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
The research method is done by first determining the object of research, population and sample and data collection techniques. In this research the type used is secondary data. The research method is to use quantitative analysis which analyzes by means of description, classical assumption test, regression analysis and data hypothesis testing using SPSS Version 26 software.The results of this study indicate that Cash Turnover, Receivable Turnover, Inventory Turnoverand Fixed Assets Turnover simultaneously affect Profitability in Industrial and Chemical Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) Period 2016-2019. While partially Cash Turnover, Inventory Turnover and Fixed Asset Turnover affect Profitability. Meanwhile, the Receivable Turnover has no effect on the profitability of Industrial and Chemical Manufacturing Companies listed on the Indonesia Stock Exchange (BEI) for the period of 2016-2019.